2006
DOI: 10.1002/jnr.21004
|View full text |Cite
|
Sign up to set email alerts
|

High affinity of anti‐GM1 antibodies is associated with disease onset in experimental neuropathy

Abstract: High antibody affinity has been proposed as a disease determinant factor in neuropathies associated with anti-GM1 antibodies. An experimental model of Guillain-Barré syndrome, induced by immunization of rabbits with bovine brain gangliosides or GM1, was described recently (Yuki et al. [2001] Ann. Neurol. 49:712-720). We searched plasma from these rabbits, taken at disease onset and 1 or 2 weeks prior to onset, for the presence of high-affinity anti-GM1 IgG antibodies. Affinity was estimated by soluble antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Anti-GM1 IgG antibody titers do not differ between rab- bits that develop paralysis and that do not manifest clinical findings under the same immunization protocol (van Sorge et al, 2007). Other factors such as the affinity of the antibodies may be involved in disease induction by anti-GM1 antibodies (Comín et al, 2006). Thin-layer chromatography with immunostaining confirmed the reactivity of IgG with GM1 ( Fig.…”
Section: Clinical Serological and Electrophysiological Findings Of mentioning
confidence: 61%
“…Anti-GM1 IgG antibody titers do not differ between rab- bits that develop paralysis and that do not manifest clinical findings under the same immunization protocol (van Sorge et al, 2007). Other factors such as the affinity of the antibodies may be involved in disease induction by anti-GM1 antibodies (Comín et al, 2006). Thin-layer chromatography with immunostaining confirmed the reactivity of IgG with GM1 ( Fig.…”
Section: Clinical Serological and Electrophysiological Findings Of mentioning
confidence: 61%
“…87 Plasma from rabbits, taken at disease onset and 1 or 2 weeks prior to onset, were tested for the presence of high-affinity anti-GM1 IgG antibody. 11 Affinity was estimated from soluble antigen-binding inhibition. High-affinity antibodies (binding inhibition by 10 Ϫ9 M GM1) were detected at disease onset but not before.…”
Section: Animal Models Of Acute Motor Axonal Neuropathymentioning
confidence: 99%
“…Rabbits which developed the neuropathy showed higher titers of monospecific and high-affinity anti-GM1 antibodies which were detectable even four weeks before the onset of the neuropathy. High-affinity antibodies were also demonstrated in a previous study in rabbits immunized with GM1 and KLH which developed the neuropathy, but these antibodies were not searched in the unaffected rabbits immunized with the same procedure [20]. More recently it was reported that rabbits, immunized with GM1 and KLH, which developed an axonal neuropathy had highaffinity antibodies, whereas the only rabbit immunized with the same procedure, which did not developed the neuropathy did not have highaffinity antibodies [18].…”
Section: Discussionmentioning
confidence: 75%
“…Binding inhibition of anti-GM1 monospecific antibodies to solidphase adsorbed GM1 by soluble GM1 was calculated: OD of the wells containing the complex with soluble GM1 and anti-GM1 monospecific antibodies/OD of the wells with anti-GM1 monospecific antibodies (%). Anti-GM1 were judged high-affinity antibodies in the presence of binding inhibition by 10 − 9 M soluble GM1 [20].…”
Section: Soluble Antigen Binding Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation